Defining Fuzzy Membership Function for Fuzzy Data Warehouses - Asanka, Dinesh; Perera, Amal Shehan (2018 4th International Conference for Convergence in Technology (I2CT), 2018)
Data warehouse is used in many organization as a tool to gain competitive advantage over their competitors. However, in most data warehouse implementations, lot of assumptions are made. By making assumptions, outcome of data warehouse is little far from the truth. Also, these assumptions will veracity of data warehouse is questionable. To avoid veracity of data warehouse, fuzzy logic can be incorporated. In fuzzy logic, fuzzy membership function plays a huge role hence in case of fuzzy data warehouse, fuzzy membership plays a key role as well. In data warehouse, different types of fuzzy membership functions can be introduced. arbitrary, data driven, linguistic, derived, survey-based membership functions are introduced in this research paper for different cases in data warehouse.